Project network SDN, for providers ISP - Одарченко, Р. С.; Даков, С.Ю. (Science-based technologies, 2017)
The work analyzes the relevance SDN application for ISP provider. It was built model use Internet services using SDR and SDN and optical network OTS. What used to supply stationary and mobile internet. Proposed examples of equipment and software. Calculated the cost of the hardware and software of the program - controlled network.